Helping students take control of their learning through the use of focused weekly review sheets - Gunn, Cindy (2001)
This paper reports on work done with students enrolled in a Level 4 Certificate of Attainment in English (CAEL) class at the University of Waikato Language Institute in Auckland. The original purpose was to help raise the students' awareness of the role they are taking to learn English through the use of weekly review sheets. However, ongoing analysis of the data revealed that in addition to focusing the students on reflecting on what they had learned and how they learned, the weekly review sheets became a vehicle for student-teacher dialogue.